Efficacy and safety of proactive treatment with twice-weekly topical Cal/BD foam in patients with plaque psoriasis undergoing HPA-axis testing: a PSO-LONG subgroup analysis. (19th May 2022) - Papp, Kim; Adamski, Zygmunt; Guenther, Lyn; Liljedahl, Monika; Miasik-Pogodzinska, Agnieszka; Szponar-Bojda, Anna; Lynde, Charles; Nutt, Terri; Mørch, Marie Holst; Tyring, Stephen; Werschler, William; Reich, Adam; et al.
Abstract: Objective: In PSO-LONG, long-term proactive management (PAM) of psoriasis with fixed-dose combination calcipotriol 50 µg/g and betamethasone dipropionate 0.5 mg/g (Cal/BD) aerosol foam was superior to conventional reactive management. This post-hoc analysis investigated long-term PAM with Cal/BD foam in PSO-LONG patients who could be more susceptible to corticosteroid-induced hypothalamic-pituitary-adrenal (HPA) axis suppression. Methods: Efficacy and safety of PAM with Cal/BD foam (twice-weekly) versus reactive management (twice-weekly vehicle foam), with once-daily rescue Cal/BD foam for four weeks following relapse, was assessed in the HPA subgroup ( n  = 66); patients had moderate-to-severe psoriasis (physician global assessment score ≥3; 10–30% body surface area affected). Primary endpoint was time to first relapse. Results: PAM with Cal/BD foam was associated with longer median time to first relapse (111 versus 31 days), reduced risk of first relapse (hazard ratio: 0.49; p  = .029), greater proportion of days in remission (17%; p  = .001) and reduced rate of relapse (60% reduction; p  < .001) than reactive management. Adverse events occurred in 37.5% (PAM) and 47.1% (reactive management) of patients, with no new safety signals. No clinically significant HPA-axis suppression was observed. Conclusion: Efficacy of PAM with Cal/BD foam is maintained in patients with moderate-to-severe psoriasis, with no new safety signals.